2022
DOI: 10.3390/ijerph19106180
|View full text |Cite
|
Sign up to set email alerts
|

Building the Foundation of Aquatic Literacy in 4–6 Years-Old Children: A Systematic Review of Good Pedagogical Practices for Children and Parents

Abstract: Children between the ages of 4–6 years represent the population most affected by drowning accidents, while their early involvement in physical activity, and more specifically in aquatic activities is a key factor in their future physical life journey. The systematic review’s purpose was to identify aspects in the intervention’s studies with children and/or their parents that had a significant impact on the Aquatic Literacy (AL) dimensions mentioned as motor, psychological, affective, and cognitive. The PICO me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…However, the study has the limitation that the logistic situation (i.e., trainer qualification, infrastructure) does not permit to include water-based activities, although aquatic experiences represent an important aspect of PL development ( 105 , 106 ). Furthermore, the children cannot be randomly assigned to the intervention and control condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study has the limitation that the logistic situation (i.e., trainer qualification, infrastructure) does not permit to include water-based activities, although aquatic experiences represent an important aspect of PL development ( 105 , 106 ). Furthermore, the children cannot be randomly assigned to the intervention and control condition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors regard mastery of the aquatic environment at an early age as a procedure related to an individual's overall development [26][27][28]. Another study revealed that the development of aquatic motor skills is the result of obtaining knowledge about the characteristics of the environment in which students develop and understand how to effectively use their bodies in the aquatic environment [29]. Thus, aquatic initiation programs that involve motor play methodologies should be promoted as a means of fostering these motor skills.…”
Section: Discussionmentioning
confidence: 99%